2006
DOI: 10.1111/j.1748-5827.2006.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical correction of abnormalities associated with brachycephalic airway obstruction syndrome in dogs in Australia

Abstract: Laryngeal collapse is relatively common in dogs presented for surgical correction of brachycephalic airway obstructive disease. Dogs with severe laryngeal collapse often respond well to surgery. Clinical signs rarely resolve completely following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
260
6
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(301 citation statements)
references
References 6 publications
24
260
6
11
Order By: Relevance
“…This dog had a left-sided cricoarytenoid lateralization along with caudal staphylectomy and sacculectomy and also required a temporary tracheostomy after surgery. Dogs evaluated for grades 2 and 3 laryngeal collapse have been reported to have a 83% to 100% survival rate in the postoperative period if a temporary tracheostomy was performed concurrently with a left-sided cricoarytenoid lateralization (6,16). Unlike these previous reports, this dog was only responsive to mechanical ventilation.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This dog had a left-sided cricoarytenoid lateralization along with caudal staphylectomy and sacculectomy and also required a temporary tracheostomy after surgery. Dogs evaluated for grades 2 and 3 laryngeal collapse have been reported to have a 83% to 100% survival rate in the postoperative period if a temporary tracheostomy was performed concurrently with a left-sided cricoarytenoid lateralization (6,16). Unlike these previous reports, this dog was only responsive to mechanical ventilation.…”
Section: Discussionmentioning
confidence: 80%
“…The most common breed reported in our study was pugs (32%), which was higher than in previous reports (9% to 21%), and may represent a difference in regional breed distribution (1,4,7). Mean age has been previously reported as 30 to 38 mo with a range of 2.5 to 189 mo (1,4,6,7,9). The present study reported a mean age of 53 mo, which is higher than in previous reports, but was not found to be a significant risk factor for complications.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The facial and occipital skull bones become deformed, causing a myriad of undesirable medical traits collectively referred to as BAOS (brachycephalic obstructive airway syndrome) (22). This syndrome includes soft palate elongation, stenotic nares, an increased amount of tissue in the throat and submandibular area, laryngeal collapse, tracheal hypoplasia, everted laryngeal saccules with mucous membrane edema and hyperplasia (6,20,25). Because brachycephalic dogs are predisposed to BAOS, it is assumed that the risk of general anesthesia for the whole group is increased (3,13 Changes occurring during general anesthesia may persist after its completion.…”
Section: Praca Oryginalnamentioning
confidence: 99%